Clinical evaluation of low cost Indian knee prosthesis in government medical colleges - Abdul Aziz, Ansari Muqtadeer; Rathod, Pratik; Patel, Altamash (International Journal of Research in Orthopaedics, 2021)
Background: The clinical and functional outcome of total knee arthroplasty was studied using low cost Indian knee prosthesis called Destiknee by Maxx Company in government medical hospital. The objectives was to do assessment of pain relief, joint mobility and deformity correction post-operatively, pre-operative and post-operative Knee society score comparison. Methods: Patients included were those who underwent primary total knee arthroplasty in Department of Orthopaedics, GMCH Aurangabad from January 2020 to January 2021. Clinical and functional assessment was done using the Knee society score and x-rays at 3, 6 and 12 months intervals. Results: At 1 year follow up of 28 knees, there was an improvement in the average pre-op Knee society score of 53.92 to average post-op score of 86.25 and in the range of motion from 80.42 degree to 127.32 degrees and knee flexion deformity improved from 15.25 degrees to 2.17 degrees, all of which had a p value<0.05 are significant statistically. One diabetic patient with poor glycemic control had superficial infection and one developed minor pulmonary embolism which recovered with medical management. Patients had good satisfaction both in unilateral and bilateral TKA. Conclusions: TKA resulted in significant reduction in knee pain and improvement in the functional ability of patients. The results of this low cost Indian prosthesis in a government rural setup with no laminar airflow with good efficacy and minimal complications are excellent. It was a boon for the rural population suffering from knee pain.